Biopolitics, Climate Studies and Art: Contemporary artists’ response to the problem - Asensio Sanagustín, Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Since its emergence, biopolitics has been evolving towards neoliberal approaches and the construction of social engineering by means of a political agenda where the problem of climate change stands out as a relevant one. This is a problem that has mobilized the scientific community. Thanks to technological progress, different solutions are provided to stop the degradation of the planet. However, there are more and more contemporary artists who want to spread this environmental issue by means of their work in order to contribute to raising awareness in society.